Insomnia: Cara Yoga Mengatasi - I Gusti Bagus Wirawan; Ida Bagus Suatama; Ida Bagus Wiryanata (Jurnal Penelitian Agama Hindu, 2019)
Modern style of living tends to accentuate the luxury that leads to the affection of physical pleasure and sensual pleasure. This will require more variety of needs that must be fulfilled and will have an impact on the work of the mind. If not there will be condition of lack of ability to control thoughts which can arise mental pressure, anxiety and eventually become stressful. If this condition is allowed, sleep will become difficult. People who have difficulty of sleeping are called insomnia. Therefore, on this study was carried out with the title "Insomnia: How Yoga Overcome It." The formulation of the problem presented in this study concerns three things, namely 1) why do people who experience insomnia may be viewed from the yoga perspective? and 2) how does yoga overcome insomnia? Both problems are elaborated by applying the theory of yoga which was assisted by several methods. In collecting the data, the observation and the interviews were utilized, while in describing and analyzing the data, the descriptive and the interpretative method were applied. According to the study, the insomnia is part of dhuka telu 'three types of suffering /pain', namely adyatmika dhuka pain caused by inability to control the nature and fluctuations of mind '. For this reason yoga has a way of overcoming it with the practice of abhiyasa and wairagya 'patience, diligence and sincerity in practicing yoga'. The form of asanas that is very influential in overcoming insomnia is doing a series of Surya Namaskara movements with its prenatal system, relaxing by taking savasana and the Gayatri Mantram puja when starting the yoga practice and Prativi Stava when having relaxation.